"A park is not just a park": Toward counter-narratives to advance equitable green space policy in the United States. (September 2022) - Rigolon, Alessandro; Yañez, Elva; Aboelata, Manal J.; Bennett, Rachel
Abstract: Policy advocacy to address socioeconomic and racial/ethnic inequities in access to urban green space (e.g., parks) in the U.S. and elsewhere are often stymied by two dominant narratives on green space reinforced by politicians, business leaders, and mainstream media. The first argues that green space is "nice to have" but not necessary, and the second frames green space as "universally good" for economic development. In this paper, we study counter-narratives to push for equitable green space policy relying on qualitative research with 30 U.S. policy advocates about their experiences with green space equity work. We find that counter-narratives to the "nice to have" narrative could frame green space as essential, multifunctional, and resilient infrastructure. Also, counter-narratives to the "universally good" narrative could describe green space as a setting for equitable development, cultural representation and inclusiveness, and healing for people of color. Further, counter-narratives should be tailored to specific policy campaigns by targeting audiences, seizing historical opportunities (e.g., COVID-19 pandemic), and centering the stories of disadvantaged people. These findings can be interpreted through the lens of structural racism and can provide pathways forward for advocates seeking to achieve green space equity through policy change and power building. Highlights: Two dominant narratives limit policy advocacy efforts to advance green space equity. Dominant narratives frame green space as "nice to have" or "universally good". Counter-narratives could frame green space as essential, intersectional, and resilient infrastructure. Counter-narratives could describe green space as a setting for equitable development, cultural representation, and healing. Counter-narratives could target audiences, seize historical opportunities, and center disadvantaged people.